Impact of Green Finance on Environmental Protection; Empirical Evidence from Emerging Economies: (BRICS & CIVET) (KASBIT Business Journal, 2024)
Green finance is one of the modes of promoting an integrated growth of financial activities and ecological protection. Main objective of the study is to investigate the impact of green finance on environmental protection and reduction of CO2 emission in emerging economies. A balanced data set for the year 2002 to 2022 was collected for 10 emerging economies based on two groups of emerging economies as BRICS (Brazil, Russia, India, China and South Africa) and CIVET (Colombia, Indonesia, Vietnam, Egypt and Turkey). Panel data analysis has been used to ascertain empirical results. The results of the study explain that green finance has significant positive impact on environmental protection in emerging economies. The study found that an increase in green finance is associated with a decrease in carbon emissions, indicating that green finance is an effective tool for reducing carbon emissions and mitigating climate change. Overall, findings of this study suggest that green finance can play an important role in promoting environmental protection in emerging economies. The study also provides valuable insights for investors, highlighting the potential benefits of investing in green projects and companies in emerging economies.
Keywords: Green Finance; Environmental hazards; Trade; GDP per capita